The right of local communities under International Human Rights Law to access cultural heritage: case study of Barrios Altos in Lima (Peru) - Gamarra Galindo, Marco Antonio (2022)
This dissertation explains how the right of local communities to cultural heritage, under International Human Rights Law, requires States to react to its destruction by private actors during peacetime. This work is relevant because there has been attacks against cultural heritage by such actors for the realization of economic activities during times of peace, but literature on cultural heritage has generally focused on its protection in the context of armed conflicts. This research argues that this right obliges States to prevent the destruction of cultural heritage through the enforcement of laws, to effectively punish the destruction via administrative and criminal avenues, and to provide access to remedies that facilitate the participation and access to information. It applies the legal framework on the right to cultural heritage to a case study: the destruction of two historic buildings in Barrios Altos (Lima).